A reduced graphene oxide / nickel iron hydrotalcite composite heteropoly acid root catalytic oxidation electrode and a preparation method thereof

CN116791141BActive Publication Date: 2026-10-27CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310817803.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2026-10-27
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

[0005]以上方法虽然可以提升镍铁水滑石的OER活性和稳定性,但剥离过程复杂繁琐,同时需要使用有毒的甲酰胺作为溶剂

Benefits of technology

[0030](1)本发明利用rGO的优异导电性和杂多酸根对水滑石OER性能进行了显著提升;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116791141B_ABST
    Figure CN116791141B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a reduced graphene oxide / nickel-iron hydrotalcite composite heteropoly acid root water catalytic oxidation nickel foam-based electrode, and relates to the field of water catalytic oxidation electrode material design and preparation. In the application, a nickel foam electrode sheet is used as a basic electrode material, a two-step electrodeposition method is used, GO is reduced to rGO through electrodeposition on a nickel foam substrate, and then nickel-iron hydrotalcite and a composite heteropoly acid root are prepared through secondary electrodeposition, so that the catalytic oxidation electrode is finally prepared. The conductivity of rGO and the heteropoly acid root modification are used to obtain a nano array structure, construct a heterostructure, increase the reaction active site, and finally improve the catalytic oxidation performance and stability of the electrode. Meanwhile, the preparation process is simple, environmentally friendly and safe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalytic oxidation electrode technology, and in particular to a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode and its preparation method. Background Technology

[0002] Energy is a core issue in the development of human society. However, traditional fossil fuels not only cause serious environmental pollution but also suffer from limited resource constraints, making the development of renewable energy sources an urgent necessity to replace traditional energy. Among renewable energy sources, hydrogen energy, as a clean and efficient energy form, has attracted much attention. While the principle of water electrolysis for hydrogen production is simple and can produce high-purity hydrogen, the oxygen evolution reaction (OER) involves a four-electron transfer process, resulting in a large overpotential and slow reaction kinetics. Therefore, developing efficient and stable OER catalysts is of great significance for promoting the development of the hydrogen energy industry.

[0003] Currently, OER catalysts generally suffer from high cost, resource scarcity, and poor catalytic activity and stability, severely limiting their feasibility for practical application in OER. Layered double hydroxides (LDHs), consisting of two cation layers and one anion layer, are widely used in OER due to their controllable structure, tunable electronic structure, and good electrochemical activity. However, nickel-iron LDHs exhibit poor intrinsic conductivity, insufficient exposure of active sites, and a limited number of active sites, resulting in poor cycle stability and limiting their development in the catalyst field.

[0004] To address the aforementioned issues, researchers have modified nickel-iron hydrotalcite using methods such as exfoliation, composite formation, and in-situ growth to obtain highly efficient and durable OER catalysts. Song et al. [Song F, Hu X. Nat. Commun., 2014, 5(1): 4477.] first synthesized hydrotalcite nanosheets using a liquid-phase exfoliation method. This method involved exfoliating multiple layers of hydrotalcite to fully expose the active sites of the hydrotalcite layers, while ensuring sufficient contact between the substrate and the electrolyte, which is beneficial for the OH groups near the electrode during the electrolysis process. - This mass transfer mechanism avoids catalyst dissolution caused by localized acidification, thus preventing a decrease in its stability. After exfoliation, the nickel-iron hydrotalcite exhibits good mass transfer at 10 mA cm⁻¹. -1 The overpotential decreased from 347mV to 302mV. Wang et al. [Wang ZQ, Zeng S, Liu WH, Wang XW, Li QW, Zhao ZG, Geng F X. ACS Appl. Mater. Interfaces, 2017, 9(2): 1488.] grew NiCo2O4 arrays on nickel foam using a two-step hydrothermal method, followed by loading nickel-iron hydrotalcite sheets. A large amount of Ni 2+and Ni 3+ Electron transfer facilitates charge transport, and the interfacial coupling between NiCo2O4 and nickel-iron hydrotalcite introduces more active sites. (Current density 50 mA cm⁻¹) -1 With an overpotential of 290mV, the current did not decrease significantly after working at 300mV for 10 hours.

[0005] While the above methods can improve the OER activity and stability of nickel-iron hydrotalcite, the exfoliation process is complex and cumbersome, and requires the use of toxic formamide as a solvent. Furthermore, hydrothermal in-situ growth on nickel foam, although increasing conductivity, involves long reaction times and complex conditions. Therefore, finding a simple, efficient, and environmentally friendly way to improve the OER performance and stability of catalytic oxidation electrodes and introduce new active sites is one of the important problems that needs to be solved. Summary of the Invention

[0006] To address the aforementioned issues, this invention leverages the excellent conductivity of rGO and the enhancing effect of heteropolyacids on the OER performance of hydrotalcite. A two-step electrodeposition process is employed: first, rGO is deposited on a nickel foam electrode for modification; then, electrodeposition simultaneously grows nickel-iron hydrotalcite and composites heteropolyacids. The electrode surface prepared by this invention features a regular array of hydrotalcite nanosheets, introducing new active sites and resulting in excellent OER performance and stability.

[0007] The preparation method of the reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode of the present invention includes the following steps:

[0008] S1. Remove surface oxides from the foamed nickel electrode sheet using hydrochloric acid;

[0009] S2. Graphene oxide was dispersed in PBS buffer and deposited on the surface of a nickel foam electrode using cyclic voltammetry. After deposition, the electrode surface was rinsed with deionized water and dried to obtain a nickel foam electrode with rGO deposited on it.

[0010] In S2, the reduction and deposition of graphene oxide on the electrode can increase the stability and conductivity of the subsequent LDH deposition. Potential selection allows the reduction reaction to occur on the working electrode. The scanning speed and cycle can affect the morphology, size and total mass of rGO on the nickel foam surface.

[0011] S3. The nickel foam electrode with deposited rGO is placed in an electrolyte containing heteropolyacids, and cyclic voltammetry is used to deposit the rGO on the electrode surface. After the deposition is completed, the electrode surface is rinsed with deionized water and then dried to obtain a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode.

[0012] Furthermore, in S1, the thickness of the nickel foam electrode sheet is 0.3 to 1 mm, and the size is 1 cm × 1 cm.

[0013] Furthermore, in S1, the concentration of hydrochloric acid is 2M.

[0014] Furthermore, in S2, the pH of the PBS buffer is 7.4.

[0015] Furthermore, in S2, the weight-to-volume ratio of graphene oxide to PBS buffer is 5–15 mg: 50 mL.

[0016] Furthermore, in S2, the deposition potential range of the cyclic voltammetry is -1.20V to -1.6V (high potential) and 0.5V to 0.7V (low potential), and the scan rate is 20 to 30 mV / s. -1 The deposition cycle is 15 to 25 cycles.

[0017] Furthermore, in step S2, the drying temperature is 50°C and the drying time is ≥6 hours. This invention does not strictly limit the drying time; the material only needs to be completely dried.

[0018] Furthermore, in S3, the electrolyte containing heteropolyacids is composed of nickel nitrate, ferric nitrate, and heteropolyacid salts.

[0019] Further, in step S3, the concentration of nickel nitrate in the electrolyte is 20-60 mM, the concentration of ferric nitrate is 20-60 mM, the concentration of heteropoly acid is 0.03-0.08 mM, and the remainder is water.

[0020] Furthermore, the heteropolyacid salt is one or more of sodium phosphotungstate, sodium phosphotomolybdate, sodium silicotungstate, and sodium silicotomolybdate.

[0021] Furthermore, in S3, the deposition potential range of the cyclic voltammetry is -1.20 to -1.4V for high potential and 0 to 0.20V for low potential, and the scan rate is 5 to 10 mVs. -1 The deposition cycle is 3 to 6 cycles.

[0022] Furthermore, in step S3, the drying temperature is 50°C and the drying time is 6h to 12h.

[0023] This invention provides a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode prepared according to the above method.

[0024] In this invention, four design aspects enhance the electrochemical catalytic oxidation performance of the electrode:

[0025] (1) rGO is laid flat on a nickel foam substrate and forms a heterostructure with nickel-iron hydrotalcite (LDH) that is subsequently deposited on the nickel foam substrate, which improves the problem of poor conductivity of LDH.

[0026] (2) Hydroxide ions near the nickel foam electrode react with nickel-iron ions in the electrolyte to form nickel-iron hydrotalcite (NiFe-LDH) on the electrode surface. Due to the presence of heteropoly acid ions, the deposited hydrotalcite nanosheets grow vertically, and Keggin-structured heteropoly acid ions are inserted into the LDH interlayer, thereby exposing more active sites.

[0027] (3) The composite of heteropoly acid radicals with high-valence metal cations (W, Mo) introduces new active sites to the catalyst. The high-valence metal ions increase the average binding energy of Ni and Fe and reduce the charge transfer resistance.

[0028] (4) By adjusting the electrodeposition process parameters, the size and morphology of the catalyst were effectively controlled, thereby stimulating the scale efficiency of nanomaterials. Under the combined effect of these factors, the present invention obtains an OER electrode with good conductivity, high activity, and stability.

[0029] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0030] (1) This invention utilizes the excellent conductivity and heteropoly acid anions of rGO to significantly improve the OER performance of hydrotalcite.

[0031] (2) The present invention uses reduced graphene oxide modified nickel foam as a substrate and prepares a deposition electrode with a heteropolyacid complex and a nano-hydrotalcite sheet array by a simple electrodeposition method.

[0032] (3) The preparation process of the electrode of the present invention is simple and the reaction conditions are easy to control. No toxic raw materials are used in the preparation process, thus realizing the green, safe and environmentally friendly preparation of the material. Attached Figure Description

[0033] The present invention will be further described below with reference to the accompanying drawings.

[0034] Figure 1 The X-ray diffraction phase analysis patterns (XRD) of the electrode (NF@rGO-LDH-PW) of Example 1 and the electrode (NF@rGO) of Comparative Example 1 are shown below.

[0035] Figure 2 Linear scanning voltammetry (LSV) scans of the electrode (NF@rGO-LDH-PW) in Embodiment 1 and the electrode (NF@rGO) in Comparative Example 1 of this invention;

[0036] Figure 3 The images shown are scanning electron microscope (SEM) images of the electrode (NF@rGO-LDH-PW) of Embodiment 1 of the present invention, where (a) is 0.5kx, (b) is 15.0kx, (c) is 100kx, and (d) is EDS approximation. Detailed Implementation

[0037] The technical solution provided by the present invention will be further described below with reference to the embodiments.

[0038] The raw materials and equipment used in the specific embodiments of the present invention are as follows:

[0039] Deposition system: a three-electrode system, with a platinum clamp and nickel foam (NF) as the working electrode, a 10mm × 10mm graphite electrode as the auxiliary electrode, and a saturated calomel electrode as the reference electrode; nickel foam: purity 99.8%, thickness 0.3mm, pore size 0.2mm-0.6mm, porosity 97.2%; graphene oxide: analytical grade; phosphate buffered PBS (pH = 7.4); nickel nitrate hexahydrate: analytical grade; ferric nitrate nonahydrate: analytical grade; heteropolyacids: provided by heteropolyacid salts, which can be dispersed in an electrolyte containing NiFe ions, wherein the heteropolyacid salts are one or more of sodium phosphotungstate, sodium phosphomolybdate, sodium silicotungstate, or sodium silicotungstate.

[0040] Example 1

[0041] (1) Cut 0.3mm thick nickel foam into 1cm×1cm electrode sheets and clean the nickel foam (NF) with 2M hydrochloric acid to remove oxides from the electrode surface;

[0042] (2) 15 mg of graphene oxide was dispersed in 50 mL of PBS buffer (pH 7.4) and deposited using cyclic voltammetry in a potential range of -1.40 V to 0.60 V at a scan rate of 30 mV / s. -1 After 20 deposition cycles, the electrode surface was rinsed with deionized water and dried in a vacuum drying oven at 50°C for 6 hours to obtain a nickel foam electrode with deposited rGO.

[0043] (3) The electrolyte used was 60 mM nickel nitrate, 20 mM ferric nitrate, and 0.06 mM sodium phosphotungstate. Cyclic voltammetry was used for deposition in a potential range of -1.30 V to 0.10 V at a scan rate of 5 mV / s. -1 A total of 3 cycles were performed, followed by rinsing at 50°C and drying for 6 hours to obtain the deposited catalytic electrode NF@rGO-LDH-PW.

[0044] Electrochemical performance tests of the deposited catalytic electrode showed that the catalytic electrode could achieve electrochemical conductivity at 10 mA / cm². -1 The overpotential at the current density is 223 mV, and the Tafel slope is 33 mVdec. -1 At 20mAcm -1 The voltage increased by 0.67% after 12 hours of energizing at the current density.

[0045] Comparative Example 1

[0046] Same as Example 1, except that phosphotungstic acid was not added, resulting in the deposited catalytic electrode NF@rGO-LDH. The comparison catalytic electrode at 10 mA / cm²... -1 The overpotential at the current density is 309.5 mV, and the Tafel slope is 81 mVdec. -1 At 20mAcm -1 After 12 hours of energizing at the current density, the voltage increased by 13.82%. This indicates that without the addition of heteropolyacids, the OER activity and stability decrease.

[0047] The phase analysis of the product NF@rGO-LDH-PW obtained in Example 1 and the product NF@rGO obtained in Comparative Example 1 is as follows: Figure 1 As shown, LSV is as Figure 2 As shown. Morphological analysis of Example 1 is as follows. Figure 3 As shown.

[0048] Example 2

[0049] (1) Cut 0.3mm thick nickel foam into 1cm×1cm electrode sheets and clean the nickel foam (NF) with 2M hydrochloric acid to remove oxides from the electrode surface;

[0050] (2) 10 mg of graphene oxide was dispersed in 50 mL of PBS buffer (pH 7.4) and deposited using cyclic voltammetry in a potential range of -1.40 V to 0.60 V at a scan rate of 20 mV / s. -1 After 20 deposition cycles, the electrode surface was rinsed with deionized water and dried in a vacuum drying oven at 50°C for 6 hours to obtain a nickel foam electrode with deposited rGO.

[0051] (3) The electrolyte used was 60 mM nickel nitrate, 20 mM ferric nitrate, and 0.06 mM sodium phosphotungstate. Cyclic voltammetry was used for deposition in a potential range of -1.40 V to 0.10 V at a scan rate of 10 mV / s. -1 A total of 4 cycles were performed, followed by rinsing at 50°C and drying for 6 hours to obtain the deposited catalytic electrode NF@rGO-LDH-PW.

[0052] Electrochemical performance tests of the deposited catalytic electrode showed that the catalytic electrode could achieve electrochemical conductivity at 10 mA / cm². -1 The overpotential at the current density is 265mV, and the Tafel slope is 56mVdec. -1 At 20mAcm -1 The voltage increased by 3.41% after 12 hours of energizing at the current density.

[0053] Comparative Example 2

[0054] Same as Example 2, except that GO was not added, resulting in the deposited catalytic electrode NF@LDH-PW. Electrochemical performance testing of this deposited catalytic electrode showed that the catalytic electrode performed well at 10 mA / cm². -1 The overpotential at the current density is 315mV, and the Tafel slope is 87mVdec. -1 At 20mAcm -1 After 12 hours of energization at the current density, the voltage increased by 10.24%, indicating that the stability of nickel foam without rGO modification decreased significantly.

[0055] Example 3

[0056] (1) Cut 0.3mm thick nickel foam into 1cm×1cm electrode sheets and clean the nickel foam (NF) with 2M hydrochloric acid to remove oxides from the electrode surface;

[0057] (2) 20 mg of graphene oxide was dispersed in 50 mL of PBS buffer (pH 7.4) and deposited using cyclic voltammetry in a potential range of -1.60 V to 0.70 V at a scan rate of 25 mV / s. -1 After 20 deposition cycles, the electrode surface was rinsed with deionized water and dried in a vacuum drying oven at 50°C for 10 hours to obtain a nickel foam electrode with deposited rGO.

[0058] (3) The electrolyte used was 40 mM nickel nitrate, 40 mM ferric nitrate, and 0.03 mM sodium phosphotungstate. Cyclic voltammetry was used for deposition in a potential range of -1.30 V to 0.20 V at a scan rate of 10 mV / s. -1 A total of 6 cycles were performed, followed by rinsing at 50°C and drying for 10 hours to obtain the deposited catalytic electrode NF@rGO-LDH-PW.

[0059] Electrochemical performance tests of the deposited catalytic electrode showed that the catalytic electrode could achieve electrochemical conductivity at 10 mA / cm². -1 The overpotential at current density is 273 mV, and the Tafel slope is 64 mVdec. -1 At 20mAcm -1 The voltage increased by 5.42% after 12 hours of energizing at the current density.

[0060] Example 4

[0061] (1) Cut 0.3mm thick nickel foam into 1cm×1cm electrode sheets and clean the nickel foam (NF) with 2M hydrochloric acid to remove oxides from the electrode surface;

[0062] (2) 10 mg of graphene oxide was dispersed in 50 mL of PBS buffer (pH 7.4) and deposited using cyclic voltammetry in a potential range of -1.60 V to 0.70 V at a scan rate of 30 mV / s. -1After 25 deposition cycles, the electrode surface was rinsed with deionized water and dried in a vacuum drying oven at 50°C for 8 hours to obtain a nickel foam electrode with deposited rGO.

[0063] (3) The electrolyte used was 40 mM nickel nitrate, 40 mM ferric nitrate, and 0.03 mM sodium phosphotungstate. Cyclic voltammetry was used for deposition in a potential range of -1.40 V to 0.10 V at a scan rate of 5 mV / s. -1 A total of 3 cycles were performed, including rinsing at 50°C and drying for 8 hours, after which the deposited catalytic electrode NF@rGO-LDH-PW was obtained.

[0064] Electrochemical performance tests of the deposited catalytic electrode showed that the catalytic electrode could achieve electrochemical conductivity at 10 mA / cm². -1 The overpotential at the current density is 285mV, and the Tafel slope is 77mVdec. -1 At 20mAcm -1 The voltage increased by 0.81% after 8 hours of energizing at the current density.

[0065] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. Furthermore, those skilled in the art will recognize that, based on the ideas of the present invention, there will be changes in the specific implementation methods and application scope. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A method for preparing a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode, characterized in that, Includes the following steps: S1. Clean the foamed nickel electrode sheet with hydrochloric acid to remove surface oxides; S2. Graphene oxide was dispersed in PBS buffer and deposited on the surface of a nickel foam electrode using cyclic voltammetry. After deposition, the electrode surface was rinsed with deionized water and dried to obtain a nickel foam electrode with reduced graphene oxide deposited on it. The deposition potential range of the cyclic voltammetry method is -1.20 V to -1.6 V (high potential) and 0.5 V to 0.7 V (low potential), with a scan rate of 20 to 30 mV / s. -1 The deposition cycle is 15 to 25 cycles; S3. The foamed nickel electrode with deposited reduced graphene oxide is placed in an electrolyte containing heteropolyacid salts, nickel salts, and iron salts. Cyclic voltammetry is used to deposit the electrode surface. After deposition, the electrode surface is rinsed with deionized water and dried to obtain a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode. The heteropolyacid salt is one or more of sodium phosphotungstate, sodium phosphomolybdate, sodium silicotungstate, and sodium molybdate.

2. The method for preparing a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode according to claim 1, characterized in that, In S1, the thickness of the nickel foam electrode sheet is 0.3~1 mm, and the size is 1 cm × 1 cm.

3. The method for preparing a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode according to claim 1, characterized in that, In S1, the concentration of hydrochloric acid is 2 M.

4. The method for preparing a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode according to claim 1, characterized in that, In S2, the pH of the PBS buffer is 7.

4.

5. The method for preparing a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode according to claim 1, characterized in that, In S2, the weight-to-volume ratio of graphene oxide to PBS buffer is 5-15 mg: 50 mL.

6. The method for preparing a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode according to claim 1, characterized in that, In step S3, the electrolyte contains nickel nitrate at a concentration of 20-60 mM, ferric nitrate at a concentration of 20-60 mM, heteropolyacid salt at a concentration of 0.03-0.08 mM, and the remainder is water.

7. The method for preparing a reduced graphene oxide / nickel-iron hydrotalcite composite heteropolyacid catalytic oxidation electrode according to claim 1, characterized in that, In step S3, the deposition potential range of the cyclic voltammetry is -1.20 to -1.4 V (high potential) and 0 to 0.20 V (low potential), and the scan rate is 5 to 10 mV / s. -1 The deposition cycle is 3 to 6 cycles.

Citation Information

Patent Citations

  • Electrically-controlled ionic membrane material for separating phosphate ions in water and preparation method of electrically-controlled ionic membrane material

    CN114229969A

  • Three-dimensional NiFe-LDH / rGO-coated NF catalytic material for fuel cell and preparation method thereof

    CN114388823A